Incidence and spontaneous clearance of gonorrhea and chlamydia infections among men who have sex with men: a prospective cohort study in Zhuhai, China - Lyu, Hang; Tang, Haotong; Feng, Yunlong; Hu, Shuyan; Wang, Yuyu; Zhou, Lanlan; Huang, Shanzi; Li, Jiarun; Zhu, Huamei; He, Xi; Tang, Weiming; Zhou, Yi; et al. (Frontiers in Public Health, 2024)
Background Men who have sex with men (MSM) face significant risks of Chlamydia trachomatis (CT) and/or Neisseria gonorrhoeae (NG) infection. Nevertheless, only limited studies have looked into the site-specific infection and clearance of CT/NG. In order to prevent transmission, it is essential to understand the underlying factors that drive infection and spontaneous clearance. Methods A 12-week cohort study examined the association between CT/NG infection, self-clearance, and sexual behaviors among MSM. The Willingness Service recruited participants who completed weekly questionnaires and provided urine, throat, and rectal swab samples. Results The study involved 151 men, in which 51 (33.8%) were diagnosed with CT/NG infection during the study period. HIV (OR = 11.31), kissing (OR = 1.59), receptive oral sex (OR = 36.64), and insertive anal sex (OR = 19.73) constituted significant risk factors. 100% condom use (OR = 5.78) and antibiotic (OR = 7.53) were more likely to cause spontaneous clearance. Discussion MSM may engage in riskier sexual behaviors due to insufficient knowledge and awareness of STI prevention, leading to increased susceptibility to NG/CT. It is crucial to concentrate on enhancing health education for MSM. Conclusion This study found that the rectum was the most prevalent site of CT/NG and sexual behavior can influence the infection. Additionally, the appropriate use of antibiotics and consistent condom use may contribute to clear spontaneously.